Elastic wave propagation and generation in seismology - Pujol, Jose, 1945- (Cambridge University Press, 2003)
This text bridges the gap between introductory textbooks and advanced monographs by providing the necessary mathematical tools to tackle seismological problems, and demonstrating how to apply them. Complete with student exercises, this book will appeal to advanced undergraduate and graduate students, as well as researchers wishing to revisit the fundamentals.